2012
DOI: 10.5152/balkanmedj.2012.035
|View full text |Cite
|
Sign up to set email alerts
|

Association of tobacco products use and Diabetes Mellitus -Results of a National Survey among Adults in Saudi Arabia

Abstract: Objective: To compare the tobacco products use patterns of known diabetics and non diabetics. Material and Methods:A community-based cross-sectional study using STEPwise approach among adults using a multistage, stratified, cluster random sample. Data was collected using a questionnaire which included sociodemographics; tobacco products use habits, history of diabetes, biochemical and anthropometric measurements.Results: Of the total of 4654 subjects who participated in the study, 1016 (21.8%) were ever smoked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…A variety of epidemiological studies have demonstrated associations between cigarette smoking and the development of T2D [68]. The Health Professionals’ Follow-Up Study analyzed data from over 40,000 American male health care professionals who were followed with biannual surveys for over six years from 1986–1992.…”
Section: Epidemiological Evidence Linking Cigarette Smoking and Diabetesmentioning
confidence: 99%
“…A variety of epidemiological studies have demonstrated associations between cigarette smoking and the development of T2D [68]. The Health Professionals’ Follow-Up Study analyzed data from over 40,000 American male health care professionals who were followed with biannual surveys for over six years from 1986–1992.…”
Section: Epidemiological Evidence Linking Cigarette Smoking and Diabetesmentioning
confidence: 99%
“…[123] Diabetes causes morbidity and mortality with acute complications and affects adversely the quality of life with chronic complications. DM is an endocrine disease that can be seen at any age, is spreading rapidly in our country and around the world, costs too high treatment and causes so many problems due to its important complications.…”
Section: Introductionmentioning
confidence: 99%
“…DM is an endocrine disease that can be seen at any age, is spreading rapidly in our country and around the world, costs too high treatment and causes so many problems due to its important complications. [123]…”
Section: Introductionmentioning
confidence: 99%
“…A regional study done in 2012 explores this relationship using data collected through a population-based survey [1]. The study is an example of how effectively the data collected through a cross-sectional survey can be used to address various population-level health issues.…”
Section: To the Editormentioning
confidence: 99%
“…The study is an example of how effectively the data collected through a cross-sectional survey can be used to address various population-level health issues. This article examines a positive relationship between tobacco use and development of diabetes [1]. This is an interesting relationship which has also been examined in another regional cross-sectional study; however, no significant results were found at different levels of smoking use [2].…”
mentioning
confidence: 95%